Improvement of Cycling Performance of Na2/3Co2/3Mn1/3O2 Cathode by PEDOT/PSS Surface Coating for Na Ion Batteries - Yatim Lailun Ni’mah; Ju Hsiang Cheng; Ming Yao Cheng; Wei Nien Su; Bing Joe Hwang (Universitas Gadjah Mada, 2018)
The surface-modified Na2/3Co2/3Mn1/3O2 is coated with a conductive Poly (3,4-Ethylene dioxy thiophene)-poly (styrene sulfonate) (PEDOT/PSS) polymer, and their resulting electrochemical properties were investigated as Na-ion battery cathode. The surface-modified Na2/3Co2/3Mn1/3O2 cathode material exhibits a high discharge capacity and good rate capability due to enhanced electron transport by surface PEDOT/PSS. The presence of PEDOT/PSS surface layer suppresses the growth of a resistive layer, while the dissolution of transition metals of the active cathode materials is inhibited as well. The resulting surface-modified Na2/3Co2/3Mn1/3O2 shows superior cycling performance, which is much stable than the pristine one as being the Na-ion battery cathode.